Bioinformatics : principles and applications - Ghosh, Zhumur (Oxford higher education, 2008)
Bioinformatics: Principles and Applications is a comprehensive text designed to cater to the needs of undergraduate and postgraduate students of biotechnology and bioinformatics. This book will also cater to the requirements of students pursuing short-term diploma as also DOEACC courses in bioinformatics